A cocktail of 165Er(iii) and Gd(iii) complexes for quantitative detection of zinc using SPECT and MRI. Issue 55 (23rd May 2018) - Malikidogo, Kyangwi P.; Da Silva, Isidro; Morfin, Jean-François; Lacerda, Sara; Barantin, Laurent; Sauvage, Thierry; Sobilo, Julien; Lerondel, Stéphanie; Tóth, Éva; Bonnet, Célia S.
Abstract : Quantitative zinc determination by nuclear and MR imaging using two Ln 3+ complexes, including purified 165 Er 3+, indispensable for metal ion quantification. Abstract : We propose quantitative assessment of zinc by combining nuclear and MR imaging. We use a cocktail of a Gd 3+ -complex providing a Zn 2+ -dependent MRI response and its 165 Er 3+ analogue allowing for concentration assessment. 165 Er is readily obtained in a cyclotron and purified, which is indispensable for successful quantification of metal ions.